THE RELATION OF LONG PARTS OF FRONT AND REAR LEGS ON BALI CATLE WITH HER NEWBORN CALVES - Susanta, I Made Edy; Sampurna, I Putu; Suatha, I Ketut (Buletin Veteriner Udayana, 2016)
This study aims were to determine the relationship between the parts of the front and rear foot length of bali calf with its parent. The object of the research consisted of 30 breeding calves and 30 individuals namely 15 male and female newborn respectively. Data in the form of measures footlong pieces of stem and parts of the calf leg length were analyzed using linear regression analysis. To determine whether there are differences between the parts of the front and rear foot length between the male with the female calf in a test with test T. The greater the ratio shows the development of long pieces of front and rear legs shows the earlier development. At birth the sizeof the back foot bottom, middle and top of the calf males and females, 63.7%, 46.5%, and 43.5% respectively of the size of its parent. Similarly, the size of the front foot down the middle and upperparts, 59.2%, 46.7%, and 44.9% respectively of the size of its parent. Development of parts of the front and rear leg starting from the bottom, middle and last at the top.
Keywords: bali cattle; calf; parts of legs; gender